(untitled) (Altre Modernità, 2019)
In this paper, the characteristics of audiovisual narco-narco narratives are presented; some of its characteristics are pointed out as well as the importance of its study within the contemporary political culture, particularly in Mexico. After the apparent diversity and heterogeneity there is a series of reiterations as are the main characters of these narratives and their basic features, which are described and exemplified in some cases. In the second part, as an example of how the thematic of drug trafficking in the audiovisual industry has evolved, the case of the cinema is placed and some differences are mentioned with the case of the narco soap operas. In the third part we summarize the theoretical debate between the relationship between the State and drug trafficking and human rights, for this we propose another relationship crossed by the study of bio-necro power, we propose here as an axis of discussion the characterization of the neoliberal state as weak and absent, versus other perspectives that grant the State the application of its disciplinary policy. Finally, we review the characteristics of narco narratives in light of what we consider a cultural tension between the premodern, modern and postmodern component that can be found, to conclude on the shortcomings and limitations of narco audiovisual stories.